ChemInform Abstract: A Click Chemistry Approach to 5, 5′‐Disubstituted‐3, 3′‐bisisoxazoles from Dichloroglyoxime and Alkynes: Luminescent Organometallic Iridium and Rhenium Bisisoxazole Complexes. Issue 47 (4th November 2013) - Van der Peet, Phillip L.; Connell, Timothy U.; Gunawan, Christian; White, Jonathan M.; Donnelly, Paul S.; Williams, Spencer J.
Abstract Bisisoxazoles are prepared in one step by the dropwise addition of aqueous potassium hydrogen carbonate to a mixture of dichloroglyoxime and terminal alkynes.